Analisis Karakteristik Aliran Fluida pada Sambungan Pipa PVC dan Pipa Besi dengan Belokan 90° - Antaria, Sukmasari; Amir Zainuddin, Muh.; Nasrullah; Arramadana, Rifky (Jurnal Karajata Engineering, 2026)
Fluid flow in piping systems with elbow joints often causes changes in flow characteristics that can lead to energy loss, so it is important to analyze this in the design of efficient piping systems. This study aims to analyze the characteristics of fluid flow in PVC and iron pipe joints with a 90° bend. The study was conducted experimentally from November to December 2024 using a fluid friction apparatus to observe the effect of changes in flow rate on pressure and flow velocity inside the pipe. Data were obtained by measuring the pressure upstream and downstream of the bend, then analyzed using the Reynolds number and Froude number approaches. The results showed that the characteristics of the PVC pipe joint 90° with the largest Froude number value of 0.314 while the iron pipe joint 90° with the largest Froude number value of 0.296. An increase in flow rate caused an increase in flow velocity and energy loss due to friction and changes in flow direction. The flow characteristics that occurred were in laminar and subcritical flow conditions. In addition, differences in pipe materials affect flow characteristics, with PVC pipes tending to produce less energy loss than iron pipes. The results of this study are expected to serve as a reference in the analysis and design of piping systems, particularly in the use of 90° bends.